Deciphering orbital hybridization in heterogeneous catalysis - Xiaoyang Yue; Lei Cheng; Eszter Baráth; Rajenahally V. Jagadeesh; Quanjun Xiang (Electron)
Abstract The catalytic coordinate is essentially the evolving frontier orbital interaction while feeding with catalytic materials and adsorbates under proper reaction conditions. The heterogeneous catalytic reaction mechanism involves the initial adsorption and activation of reactants, subsequent intermediate transformation, final target product desorption, and regeneration of catalytic materials. In these catalytic processes, interaction modulations in terms of orbital hybridization/coupling allow an intrinsic control on both thermodynamics and kinetics. Concerned charge transfer and redistribution, orbital splitting and rearrangement with specific orientation, and spin change and crossover pose a formidable challenge on mechanism elucidation; it is hard to precisely correlate the apparent activity and selectivity, let alone rational modulations on it. Therefore, deciphering the orbital couplings inside a catalytic round is highly desirable and the dependent descriptor further provides in‐depth insights into catalyst design at the molecule orbital level. This review hopes to provide a comprehensive understanding on orbital hybridizations, modulations, and correlated descriptors in heterogeneous catalysis.